2011
DOI: 10.3174/ajnr.a2799
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural MR Imaging in Neuropsychiatric Disorders, Part 1: Imaging Techniques and Their Application in Mild Cognitive Impairment and Alzheimer Disease

Abstract: SUMMARY:During the past decade, the application of advanced MR imaging techniques in neuropsychiatric disorders has seen a rapid increase. Disease-specific alterations in brain function can be assessed by fMRI. Structural GM and WM properties are increasingly investigated by DTI and voxel-based approaches like VBM. These methods provide neurobiologic correlates for brain architecture and function, evaluation tools for therapeutic approaches, and potential early markers for diagnosis. The aim of this review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 99 publications
1
25
0
Order By: Relevance
“…The use of quantitative MRI techniques such as voxelbased morphometry (VBM) are used to estimate the volume of specific brain structures such as the hippocampus in Alzheimer disease (AD), 40 and can be used to predict progression from mild cognitive impairment to AD. 41 Such techniques have evolved as part of the Alzheimer's Disease Neuroimaging Initiative.…”
Section: Sensitivity Of Conventional Imagingmentioning
confidence: 99%
“…The use of quantitative MRI techniques such as voxelbased morphometry (VBM) are used to estimate the volume of specific brain structures such as the hippocampus in Alzheimer disease (AD), 40 and can be used to predict progression from mild cognitive impairment to AD. 41 Such techniques have evolved as part of the Alzheimer's Disease Neuroimaging Initiative.…”
Section: Sensitivity Of Conventional Imagingmentioning
confidence: 99%
“…The majority of the previous studies in IBS investigated brain abnormalities from the aspect of regional activation during visceral distension in task design (Rapps et al, 2008; Mayer et al, 2009). Recently, resting-state functional connectivity (RSFC), a method that measures inter-regional temporal synchronization between a predefined seed region and functionally related regions at resting-state (van de Ven et al, 2004), has been increasingly used as a reliable and sensitive index in various disease populations (Mueller et al, 2012; Castellanos et al, 2013). RSFC alterations have been reported in patients with chronic pain disorders, including fibromyalgia (Jensen et al, 2012), chronic back pain (Baliki et al, 2012) and migraines (Mainero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Post mortem studies have shown that even healthy aging is accompanied by notable cortical atrophy and loss of brain weight from the sixth life decade onwards (Skullerud, 1985). This brain tissue loss is further accelerated by most neurodegenerative or neuropsychiatric disorders such that magnetic resonance imaging (MRI) in combination with morphometry offers an interesting diagnostic tool for differentiating between healthy and pathological brain changes (for an overview, see Raz and Rodrigue, 2006; Mueller et al, 2012a,b). One common approach is to evaluate the volume of gray matter (GM), white matter (WM) and cerebrospinal fluid (CSF) within structures of interest determined through manual delineation.…”
Section: Introductionmentioning
confidence: 99%